"CLASSICAL EXPERIMENTS IN CINE MUSIC" BY NAUSHAD ": ’’सिने संगीत में शास्त्रीय प्रयोग-संगीतकार स्व. नौषाद द्वारा’’ - Dubey, Aarti (International Journal of Research -GRANTHAALAYAH, 2015)
Music has a special place in various forms of music. Cine music or chitrapat music falling under this genre is the most popular among other genres. It is very popular among the masses due to its simplicity and predominance of miraculous expression. There are many reasons for the immense popularity of cine music among the masses. The word cine music is predominant and emotional. Due to this, the common man sees his feelings in him, his happiness and sorrow and he is able to see himself in the simplest form as experiencing the conditions of his personal life, through its simplicity, he feels that it is all his life Has happened or is happening in The melody of the song is not limited, like classical music it is not bound by rules, so the melodies of the songs are simple and straightforward. Even those who do not know the music, they sing it lukewarm or. संगीत के विविध रूपों में सुगम संगीत का विषिष्ट स्थान है। इस विधा के अंतर्गत आने वाला सिने संगीत या चित्रपट संगीत जनमानस में अन्य विधाओं की अपेक्षा सर्वाधिक लोकप्रिय है। अपनी सरलता चमत्कारपूर्ण अभिव्यक्ति की प्रधानता और भाव प्रवणता के कारण यह जनमानस में अत्यंत लोकप्रिय है। सिने संगीत की जनसाधारण में अत्यंत लोकप्रियता के अनेक कारण हैं। सिने संगीत शब्द प्रधान एवं भाव प्रधान होता है। इस कारण जनसामान्य को उसमें अपनी भावनाएँ अपना सुख दुःख नजर आता है और वो इसके सरलतम रूप में अपनी व्यक्तिगत जिंदगी की स्थितियों के अनुभव के रूप में अपने आपको देख पाता है, इसकी सादगी के जरिए उसे यही महसूस होता है कि यह सब उसी के जीवन में घटित हुआ है या हो रहा है। गीत की धुनों में क्लिष्टता नहीं होती, शास्त्रीय संगीत की तरह यह नियमों में बंधा नहीं रहता इसलिए गीतों की धुनें सरल और सीधी होती हैं। जिसे संगीत की जानकारी नहीं भी होती है वो भी इन्हें गुनगुना या गा लेता है।